2023
DOI: 10.1021/acs.analchem.3c01655
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-Inspired Degradation-Activation System Enables Ultrasensitive Multicolor Detection of Haloacetic Acids via Janus Perovskite Halide Exchange

Abstract: Haloacetic acids (HAAs), as representative disinfection byproducts, have the potential hazards of teratogenesis, carcinogenesis, and mutagenesis. Herein, inspired by the scavenging physiology of macrophages and taking advantage of the unique properties of perovskites, we design a biomimetic integrated three-step workflow, named the macrophage-inspired degradation-activation system (MIDAS), for the detection of HAAs in aqueous samples. First, HAAs are “devoured” by methyl t-butyl ether (MTBE) from a sample. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The proposed fluorescent biosensor achieved high sensitivities of 30 and 15 ppb for dichloroacetic acid and dibromoacetic acid, respectively (Figure 4B). 62 In conclusion, the rapid and multiple fluorescent responses of perovskite nanocrystals with analytes extremely facilitate the exploration for rapid detection technologies of some common hazards in food products, which is expected to design highperformance diagnostic tools for food practices through perovskite nanocrystals.…”
Section: Direct Fluorescent Biosensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The proposed fluorescent biosensor achieved high sensitivities of 30 and 15 ppb for dichloroacetic acid and dibromoacetic acid, respectively (Figure 4B). 62 In conclusion, the rapid and multiple fluorescent responses of perovskite nanocrystals with analytes extremely facilitate the exploration for rapid detection technologies of some common hazards in food products, which is expected to design highperformance diagnostic tools for food practices through perovskite nanocrystals.…”
Section: Direct Fluorescent Biosensorsmentioning
confidence: 99%
“…For example, Wei et al reported a macrophage-inspired degradation-activation system to determine haloacetic acids in aqueous medium based on halide exchanging reactions between the generated halogen atom and perovskite nanocrystals. The proposed fluorescent biosensor achieved high sensitivities of 30 and 15 ppb for dichloroacetic acid and dibromoacetic acid, respectively (Figure B) …”
Section: Perovskite Nanocrystals-based Biosensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Janus material has garnered significant attention. Due to its unique surface chemical composition and intricate geometric structure, it possesses diverse functionalities and exhibits remarkable adaptability in complex and dynamic application environments, rendering it extensively utilized in analytical chemistry, , medical immunology, , microelectronics technology, , and other related fields. In the course of continuous exploration, researchers have developed various methods for the preparation of Janus particles. These methods include interface protection techniques, , emulsion polymerization approaches, , microfluidic strategies, , self-assembly methodologies, , phase separation methodologies, , and other avenues, , among which emulsion polymerization is one of the commonly used methods.…”
Section: Introductionmentioning
confidence: 99%